The addition of metronomic chemotherapy does not improve outcome for canine splenic haemangiosarcoma. (12th September 2018) - Alexander, C. K.; Cronin, K. L.; Silver, M.; Gardner, H. L.; London, C.
Abstract : Objectives: To determine whether the addition of metronomic chemotherapy improved outcome for dogs with splenic haemangiosarcoma treated with splenectomy and adjuvant maximum tolerated dose chemotherapy. Materials and Methods: Medical records were examined retrospectively for dogs with splenic haemangiosarcoma that had undergone splenectomy followed by anthracycline‐based chemotherapy. Thirty‐nine dogs underwent splenectomy followed by maximum tolerated dose chemotherapy with an anthracycline, cyclophosphamide, or both (Group 1). Twenty‐two dogs underwent splenectomy followed by adjuvant maximum tolerated dose chemotherapy with an anthracycline, cyclophosphamide, or both, plus metronomic chemotherapy (Group 2). Dogs in both groups were further separated into those treated with either maximum tolerated dose anthracycline or maximum tolerated dose anthracycline and cyclophosphamide. Results: Median progression‐free survival was 165 days and median overall survival time was 180 days in Group 1. Median progression‐free survival was 185 days and median overall survival time was 212 days in Group 2. In both groups, the overall survival was shorter in dogs that had received maximum tolerated dose cyclophosphamide. Clinical Significance: The addition of metronomic to maximum tolerated dose chemotherapy protocols does not appear to improve outcome in dogs with splenic haemangiosarcoma treated with splenectomy and maximum tolerated dose chemotherapy.